2021
DOI: 10.3390/ijerph18094481
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Independent Mobility and Physical Activity during the COVID-19 Pandemic: A Qualitative Study with Families

Abstract: Children’s independent mobility (CIM) is the freedom of children to move around their neighbourhood without adult supervision and is closely related to overall physical activity participation. The COVID-19 pandemic has impacted movement behaviours for children, with evidence indicating a decrease in physical activity. The aim of this study was to explore experiences of CIM and physical activity during the COVID-19 pandemic from the perspectives of children and their parents. We completed 21 family (at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(98 citation statements)
references
References 43 publications
7
91
0
Order By: Relevance
“…Four studies identified an increase in physical activity [ 15 , 16 , 17 , 18 ], whereas six studies could detect no significant difference in physical activity behaviors before and during the pandemic [ 19 , 20 , 21 , 22 , 23 , 24 ]. Eight studies reported differentiated results with indoor and organized sports and physical activity decreasing, while non-organized and outdoor sports and physical activity increased [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies identified an increase in physical activity [ 15 , 16 , 17 , 18 ], whereas six studies could detect no significant difference in physical activity behaviors before and during the pandemic [ 19 , 20 , 21 , 22 , 23 , 24 ]. Eight studies reported differentiated results with indoor and organized sports and physical activity decreasing, while non-organized and outdoor sports and physical activity increased [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shows that public recommendations for maintaining physical activity have so far been ineffective. If an increase has been detected, it occurred in outdoor play and unstructured activities [ 15 , 26 , 29 , 30 , 31 ] or related to lower levels of national restrictions [ 17 ]. The increase in outdoor activities depends strongly on the housing environment.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the multilevel phenomenon of children's independent mobility, Figure 1 illustrates an overview of different CIM indicators. CIM also is linked with a number of socio-demographic, social, and physical environmental attributes [15]. Figure 2 shows a summary of multilevel CIM correlations based on a socio-ecological perspective.…”
Section: Children's Independent Mobilitymentioning
confidence: 99%
“…There has been a general agreement in previous research that urban planning approaches should take into account quality of life as their main goal. CIM also is linked with a number of socio-demographic, social, and physical environmental attributes [15]. Figure 2 shows a summary of multilevel CIM correlations based on a socio-ecological perspective.…”
Section: Parents' Perception Of the Neighborhoodmentioning
confidence: 99%
See 1 more Smart Citation